Light Polarization Mechanism for Chiral Methanol: Electron Spin (London Journal of Research In Science: Natural and Formal, 2023)
These is a challenge of determining the physical basis for light polarization by chiral molecules. In this paper we consider the molecule of methanol. We see that it is the electron spin that determines the polarization of light for an organic molecule. Electrons obey a wave equation; therein my lie the answer as to why an electron has a positive or negative spin. Civil Engineers don’t study Quantum Mechanics. So I leave this problem for those who do study QM. Funny, I wanted to take Modern Physics when I was in year two if my bachelor’s degree.
Keywords: Oganessian; Benzene; AT Math.; Polarization; Light; Chiral molecules; Methanol; Electron Spin; Quantum Mechanics.